The Truth About OSS-FRAND: By All Indications, Compatible Models in Standards Settings - Kappos, David J.; Harrington, Miling Y. (Science and Technology Law Review, 2019)
Open source software (“OSS”) has inevitably found its way into standards that contain standard essential patents (“SEPs”). However, some questions remain as to whether OSS licensing is inherently compatible with the FRAND licensing (“fair, reasonable, and non-discriminatory”) that governs SEPs. Some argue that a license’s compliance with the Open Source Initiative’s “Open Source Definition” (“OSD”) has always been understood to preclude patent royalties for the licensor by implicitly granting patent rights to the licensee. This Comment examines the historical record and finds no significant support for the notion that OSD-compliant licenses generally convey patent rights and thus preclude patent royalties.